Baby Diaper Recommendation Decision Support System Using SAW Method - Aprilia, Rima; Irawan, Muhammad Dedi; Irawati, Novica; Hasibuan, Aidillia Adha; Nuha, Salsabila Isnain (International Conference on Sciences Development and Technology, 2021)
The selection of baby diapers is very important for housewives which aims to avoid things that are not desirable, in the process of this decision support system there are several comparison criteria that will be a reference in the selection of baby diapers. In the process of the decision support system for choosing baby diapers using the SAW method, it aims to provide recommendations in giving baby diapers. This baby diaper decision support system is designed using a MySQL database system to test and find out the ranking of several available alternatives. The decision support system produced in this study can display the ranking of the results of SAW calculations to make housewives' considerations in choosing baby diapers